Interaction between Perivascular and Luminal Factors in Arteriovenous Fistula in Yucatan Miniswine - Xia, Fanya; Smith, Jacob; Rai, Vikrant; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2025)
Arteriovenous fistula (AVF) is created in end-stage renal disease patients for hemodialysis. AVF maturation failure is a common complication due to thrombosis and stenosis of the vessels involved in AVF. Chronic inflammation along with perivascular cuffing plays a critical role in AVF maturation failure. Luminal as well as periluminal factors with the involvement of transcription and epigenetic factors play a critical role in AVF maturation failure. Our previous study reported MYOD1, a factor associated with muscle regeneration and increased with muscle injury, as a significantly increased transcription factor in AVF arteries compared to control. This study aims to characterize the perivascular and vascular AVF tissues for the expression of MYOD1, mediators of inflammation, immune cell markers, and apoptosis markers with the hypothesis that muscle injury mediates the recruitment of immune cells and activation of apoptosis leading to increased apoptosis and vascular thrombosis and fibrosis of perivascular structures. Previously collected tissues from Yucatan miniswine were stained and analyzed, and the results revealed increased expression of mediators of inflammation, immune cell markers, and apoptosis markers in association with increased MYOD1 expression. The findings suggest an interaction between the expression of perivascular factors and luminal factors, but further investigations using in-vitro studies are needed to establish this relationship.